DARI KLASIK MENUJU KONTEMPORER : KAJIAN WAKTU SHALAT SEPANJANG MASA ANTARA FIQIH DAN SAINS - Faiz, ABD. Karim Faiz; Nur Awaliyah (UIN ALAUDDIN MAKASSAR, 2023)
One of the reasons for the variation in prayer times is the difference in the methods used in making prayer time schedules. Differences in prayer times also occur in the city of Parepare, as happened between the two large mosques in the city of Parepare, namely the Grand Mosque and the Al-Azhar Islamic Center Mosque. Based on the observations of researchers on September 20, 2022 the prayer times for the two mosques are different, for example the time for the Maghrib prayer at the Grand Mosque is 17.59 WITA and the Al-Azhar Islamic Center Mosque is 18.01 WITA. This difference is due to the method used by the Great Mosque, namely the Prayer Times of all time and the Al-Azhar Islamic Center Mosque with Contemporary Hisab Ephemeris. The researcher is then interested in studying how the method of determining the reckoning of prayer times of all time and how accurate of reckoning of prayer times of all time is the Great Mosque of Parepare City from a contemporary reckoning perspective. The method used in this research is field research method to examine the beginning of the time of prayer at the Great Mosque of Parepare City. This research aims to describe the method of prayer time throughout the period of the Great Mosque of Parepare City and to analyse the accuracy of hisab prayer time throughout the period of Parepare City from the perspective of contemporary hisab. The results showed that the prayer time of the Great Mosque of Parepare City is a few minutes faster when compared to contemporary hisab.